Eco-Anxiety and Ecological Hope in The End We Start From (2023) - Iffadah, Amelia Resti; Nabila, Nurul Isnaini Fitriatun; Masitoh, Siti (NOBEL: Journal of Literature and Language Teaching, 2025)
The global ecological crisis not only affects the physical environment but also evokes emotional responses, such as eco-anxiety, and hopes for the restoration of nature. This study examines the portrayal of emotional reactions and ecological hopes in the film The End We Start From (2023) through Glotfelty’s (1996) ecocritical framework. Using qualitative descriptive methods and narrative analysis, this study characterizes the main character and visualizes disaster as forms of ecological narrative. The analysis reveals that this film embodies ecological fear and emotional reactions to the environment through the main character’s fear, confusion, and alienation, while offering environmental hope through human solidarity and emotional resilience. This study contributes to broadening the scope of ecocriticism by integrating emotional aspects and storylines in the discussion of films about modern environmental issues.